ARKADII DRAGOMOSHCHENKO’S POETIC LANDSCAPES AS AN INSTRUMENT OF SELFQUESTIONING AND CROSS-CULTURAL DISPLACEMENT IN THE LATE SOVIET UNDERGROUND - Simone Guidetti (Filolog, 2025)
The poetry of Arkadii Dragomoshchenko (1946–2012), who spent his formative years in Ukraine and was active in the Leningrad underground of the 1970s and 1980s, represents a unique reflection of multiple cultural practices and media perspectives. Delving deeper into common assumptions of language, thought and representation, his texts encourage the reader to take a detached and reflective approach on literary texts, overcoming the strict cultural boundaries that usually confine the text and his author in space and time. This paper draws parallels between Dragomoshchenko’s pseudo-descriptive landscape poetry, Buddhist thought, classical Chinese landscape aesthetics, and Hryhorii Skovoroda’s nomadic philosophy of paradoxes. It thus illustrates how Dragomoshchenko consciously distanced himself from the predominant understanding of culture and memory within Russian so-called vtoraia kul’tura, developing his own peculiar strategy of resistance to Soviet restrictions while also managing to avoid strict dichotomies such as pervaia and vtoraia kul’tura, official and unofficial, foreign and national culture.